Assessment Preferences and Their Relationship to Learning Strategies and Orientations - Birenbaum, Menucha (Higher education, 1997)
The study investigated inter- and intra-group differences in assessment preferences among students in two academic disciplines which differ in their educational environment through examining the relationships between assessment preferences and student learning orientations and strategies. The sample consisted of 85 engineering and 87 education students in a major university in Israel. The subjects were administered the MSLQ for measuring their motivated learning strategies and the API for measuring their assessment preferences. The results indicated that individual differences in assessment preferences overshadow disciplinary group differences and that differences in assessment preferences are to a relatively large extent related to learning strategies and orientations. Implications for adaptive assessment were discussed.